Using English traditional songs to improve students' pronunciation: an action research at Duy Tien C High school - Tran, Thi Tuyet Mai (ĐHNN, 2017)
The primary aim of this minor thesis is to investigate the effectiveness of using English traditional songs in teaching pronunciation for high school students in Ha Nam. The author tries to find out whether the use of songs can help to make students’ pronu (...)